HUBUNGAN ANTARA KOMITMEN BERAGAMA DENGAN PERILAKU PROSOSIAL PADA MAHASISWA FAKULTAS PSIKOLOGI UNIVERSITAS ISLAM NEGERI SGD BANDUNG ANGKATAN 2008-2010 - Eva Ferdianti (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2013)
The aim of this research is studying correlation between religion comitment and prosocial behavior. Phenomena like selfish, working alone, being not care with others are indicators of antisocial behaviors. This research used quantitative approach. Sample are 72 students of psychology from Islamic State University Bandung studying at academic year 2008-2010. Result shows that there is positive significant correlation between religion comitment and prosocial behavior among students of psychology at Islamic State University Bandung who study at academic year 2008-2010.